Las prácticas de la evaluación y su incidencia en el desarrollo de aprendizajes significativos en los estudiantes de octavo, noveno y décimo años de educación general básica del colegio Dr. Hugo Guillermo González de la parroquia Santa Teresita del cantón Espíndola, provincia de Loja, período lectivo 2011-2012. Lineamientos alternativos - Rosales Gaona, Celinda (2014)
This research was general objective, to analyze the impact of the assessment practices that teachers implement in developing meaningful learning in students of the last three years of college EGB Dr. Hugo Guillermo Gonzalez in the parish of St. Therese of Canton Española, Loja Province. The development research was supported by the deductive method, which used it as a tool of scientific knowledge, and information analysis established findings, the inductive, was used to identify science, we analyzed the practice of evaluation and the development of meaningful learning and statistical results information, the analytical, served to make the analysis of the answers of the respondents, on matters relating to the practice of meaningful learning assessment and then draw conclusions, and, with the synthetic analysis was significant learning, allowing progress, issues and basic relationships understand a whole perspective under investigation. We conclude that assessment practices in the development of meaningful learning in students of the last three years of General Basic Education, teachers know, support and use the principles and guidelines in the teachinglearning process, the impact assessment practice in developing meaningful learning of the school investigated, and the validity of assessment practices can be evidenced when the structure effective tools according to the knowledge that the students were in the program contents in the course of study.